Efek Pemberian Ekstrak Jaloh Dikombinasi dengan Probiotik dan Kromium Terhadap Profil Hematologi dan Titer Antibodi Vaksin ND pada Ayam Broiler yang Mengalami Stres Panas - Sugito Sugito; Fakhrurrazi Fakhrurrazi; M. Isa (Jurnal Agripet, 2011)
The effect of jaloh extract combined with probiotic and chromium on the haematology profiles and ND antibody vaccine of broiler given heat stressABSTRACT. The purpose of this study is to determine the respons of chicken broiler under heat stress that given drinking water contained extract jaloh combined with probiotic and Cr mineral in the profile of haematology and antibody respons of Newcastle Disease vaccine. Twenty four of 20-day old Cobb broiler chickens were randomly assigned and devided to 6 treatment groups. Completely randomized design was used in this study. The treatments were as follows: 1) chickens under heat stress, given jaloh extract, probiotic, and chromium (P1); 2. chickens under heat stress, given jaloh extract and probiotic (P2); 3. chickens under heat stress, given jaloh extract and chromium (P3); chickens under heat stress, given jaloh extract (P4); 5. chickens under heat stress without given jaloh extract nor chromium and probiotic (P5); and 6. chickens given no heat stress and jaloh extract nor chromium and probiotic (P6). Extract jaloh dose applied is 1.000 mg/lt water, dose of probiotic is 108 cfu/lt drinking water, and chromium given in the form of chloride chromium with dose 1000 ug/lt water. Local heat stress is provided by increasing cage temperature to the range of 33.0 1C during 5 hours per day u within 15 days. Jaloh extract, probiotic, and chromium treatments in drinking water were given at 2 hour before cage temperature reaching 33 1oC and were stopped being given after 1 hour, when cage temperature back to room temperature. Blood was taken before chickens were ethanuatiated. The result suggested that giving jaloh extract to combine it with probiotic, and chromium has no significant effect in hematology profile. When combined extract jaloh with chromium (Cr), has potencial capability to stimulate improvement built of antibody (as immunomodulator) on broiler chicken heat stress.